Upaya Hukum yang Dilakukan Korban Kejahatan Dikaji dari Perspektif Sistem Peradilan Pidana dalam Putusan Mahkamah Agung Republik Indonesia - Muhammad Ridwan Lubis (UNES Law Review, 2023)
The state, via the Institute for the Protection of Witnesses and Victims (LPSK), leads the way in addressing crime victim compensation as a means of fulfilling state obligations and securing the welfare of the populace. LPSK stands for the Witness and Victim Protection Agency, an organization mandated with safeguarding the rights and safety of witnesses and/or victims. In accordance with the Law Number 13 of 2006 concerning Witness and Victim Protection, LPSK guarantees equal legal certainty. Compensation is regulated in Law Number 13 of 2006 jo. Article 28D paragraph (1) of the 1945 Constitution emphasizes that "Everyone has the right to recognition, guarantees, protection, fair legal certainty, and equal treatment before the law." Law Number 31 of 2014, PERMA (Chief Regulation) Number 1 of 2022, Government Regulation (PP) Number 8 of 2014, and PP Number 7 of 2018 are designed to provide state protection for the rights of crime victims in the UK. However, it's important to note that compensation is only available in certain cases. Additionally, the form of non-monetary compensation guaranteed by state regulation doesn't have a clear monetary value. Providing compensation to victims is a challenging task due to the lack of clarity concerning the form and scope of compensation. This will aid in ensuring that crime victims obtain certainty in their compensation rights. The state has a responsibility to revise or create regulations related to the implementation of non-monetary compensation to overcome the obstacles in resolving compensation issues. This is a study involving descriptive-analytical methods in normative legal research. The findings reveal a regulatory gap that exists in the explanation of non-monetary compensation in compensation payments. This gap creates complexity and uncertainty for the victims. The LPSK, an institution of the state, should establish a standard value as a benchmark to guarantee that victims receive proper compensation. However, compensation is not always in monetary form. The state, through LPSK, is obliged to provide compensation to protect victims' rights. To ensure consistency in payment and guarantee the protection of crime victims' rights beyond statutory classification, the government must adhere to assessments presented in various journals.